IL-8 Gene Variants and Expression in Childhood Asthma - Charrad, Rihab (Lung, 2017)
PURPOSE: To examine the IL-8 expression levels and association of genetic variants with the risk of childhood persistent asthma prognosis. METHODS: Overall, 170 asthmatic children and 170 healthy controls were included in this case–control study. The human IL-8 serum levels were measured using ELISA. The IL-8 mRNA expression levels were assessed by a real-time quantitative reverse transcription-polymerase chain reaction (qRT-PCR). The genotyping was performed by polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) methods. RESULTS: The IL-8 expression at both protein and mRNA levels was found to be significantly elevated in asthmatic children compared to healthy subjects (P < 0.0001, P = 0.004; respectively). Higher levels of IL-8 mRNA are detected in subjects with moderate to severe asthma. The presence of IL8-251 A/T (rs4073) and + 781C/T (rs2227306) polymorphisms was significantly associated with an increased risk of asthma (P = 0.002, P = 0.036, respectively). In addition, we noted a significant association between these polymorphisms and an elevated risk of atopic asthma (P < 0.05). For rs2227306 SNP, the highest median level of IgE was detected for the presence of TT genotype (865 ± 99.74 IU/mL). Although, the rs4073 polymorphism conferred a higher risk to develop asthma at an advanced stage of severity (P = 0.008). The rs4073 T and rs2227306 C alleles are considered as risk factors for asthma development. The rs4073 T allele is represented also as a risk factor for asthma severity in Tunisian children. CONCLUSIONS: Both IL-8 gene and protein expression may play a key role in asthma pathogenesis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00408-017-0058-6) contains supplementary material, which is available to authorized users.